2019
DOI: 10.3389/fneur.2019.01339
|View full text |Cite
|
Sign up to set email alerts
|

Pattern Visually Evoked Potentials in Japanese Girl With Optic Neuritis and Seropositive to Anti-myelin Oligodendrocyte Glycoprotein (MOG) Antibody

Abstract: Purpose: To describe a Japanese girl with unilateral optic neuritis who was seropositive for the anti-myelin-oligodendrocyte glycoprotein (MOG). Serial recordings of the pattern visual evoked potentials (pVEPs) were made to follow the dynamic changes of the disease activity. Observations: A 5-year-old girl developed a sudden reduction of vision and deep ocular pain in her right eye. On examination at our university hospital, the best-corrected visual acuity (BCVA) was light perception, and a swelling of the op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 24 publications
(30 reference statements)
0
2
0
Order By: Relevance
“…The studies indicate that P100 latency is more delayed in MS than NMOSD, with a greater proportion of absent responses and less frequent subclinical alterations in the latter group [22]. Prolongation of P100 latency persists after the acute phase, even when visual acuity returns to normal [23]. The characteristics of MOG-IgG positive ON in comparison to AQP4-IgG positive ON and MS-related ON are presented in Table I.…”
Section: Clinical Presentationmentioning
confidence: 98%
“…The studies indicate that P100 latency is more delayed in MS than NMOSD, with a greater proportion of absent responses and less frequent subclinical alterations in the latter group [22]. Prolongation of P100 latency persists after the acute phase, even when visual acuity returns to normal [23]. The characteristics of MOG-IgG positive ON in comparison to AQP4-IgG positive ON and MS-related ON are presented in Table I.…”
Section: Clinical Presentationmentioning
confidence: 98%
“…IVIG was used to treat acute relapses in at least 21% (128/621) of the patients in the following doses/regimens: 1-2 g/kg in 2-5 days or 400 mg/kg/day in 5 days. A single study (Takano et al, 2019) reported the use of IVIG160 mg/kg in a single dose (2.5 g). Thirty-three percent (20/61) of the studies described the use of plasma exchange (PLEX), 3 to 7 cycles, in 4% (26/621) of the patients.…”
Section: Acute Phase Treatmentsmentioning
confidence: 99%